PENTINGNYA UPSELLING DI RESERVATION SECTION FRONT OFFICE DEPARTMENT DALAM MENINGKATKAN PENDAPATAN KAMAR DI HOTEL X JAKARTA - Salsabila Chaerunnisa; Roy Daniel Samboh (Eduturisma, 2020)
The front office is, guest service department and responsible for the sale of hotel rooms based on the way that has been conducted by the reservation system. Besides that, the front office will serve guests while visitors want to stay and also provide the information details in our hotel for guests who were coming. there were several department front office such as receptionist, reservation section, guest relation officer, concierge, bell captain, telephone operators. Guests have often mistaken to differentiate reservation and receptionist. The task of the reservation is to reserve the guest bedroom. The task of the receptionist is to welcoming guests who have booked rooms and including as an information center also serving guests for a special request in the hotel. Reservation is one section that can not stand alone they must always be associated with other departments in performing their duties to fulfill special requested from guests. Being a reservation needs to have the ability such as upselling. Upselling is one type of sales in which a reservation agent will offer to prospective guests to buy the offer of the product or service in bidding higher and better in accordance with facilities will get, in an effort to make hotel gain better knowledge and income are surely rose to the hotel. the duties and responsibilities of the reservation is of course an attempt to maintain the reservations hotel room steady even increased to make income hotel still good.